Atypical Spinal Tuberculosis of Upper Thoracic Spine: A Rare Case Report - Wiguna, I Gusti Lanang Ngurah Agung Artha; Wondany, Ryan Putra; Arimbawa, Ida Bagus Gede (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Tuberculous infection is one of the most common pulmonary infection in developing countries, including Indonesia. Spinal tuberculosis is one of the most common extra¬pulmonary tuberculosis manifestation, accounting for 5% of all extrapulmonary spread, and 50% of all osteoarticular involvement. The aim of this study is to evaluate and how diagnosis and treatment to prevent over or under-diagnosis and explain about excellent management without any late complication further.Case Presentation: A 20-year-old male with a history of weakness of both of his leg for 20 days prior to admission. From these examinations, patient was then diagnosed with pathological fracture 2nd thoracic vertebral body suspected due to atypical spinal tuberculosis. Patient was then undergone surgical debridement, decompression, stabilization and fusion.Results: Patient was then undergone surgical debridement, decompression stabilization fusion. During the exposure at level C6 through Th4, no abscess was found. Transpedicular debridement at level Th2 was then done after the insertion of pedicle screws at level C6-Th1 and Th3-Th4, and again no abscess was present, however, a granulomatous mass was present on the location of 2nd thoracic vertebral body, located on the anterior right side of the spinal cord outside the dura mater.Conclusion: Atypical presentation of spinal tuberculosis with the sole clinical manifestation of neurological deficit below affected level. The definitive treatment such as surgical debridement, stabilization and fusion must be consider.Keywords: spinal, infection, tuberculosis, young patient.Correspondence: I Gusti Lanang Ngurah Agung Artha Wiguna. Division of Spine, Department of Orthopaedic & Traumatology, Prof. I.G.N.G Ngoerah Hospital, Faculty of Medicine, Udayana University, Bali, Indonesia. Email:lanangwiguna20021979@gmail.com. Mobile: 0811388859.Indonesian Journal of Medicine (2022), 07(03): 289-297https://doi.org/10.26911/theijmed.2022.07.03.05